A Case Study of the Famous Fantasia under the Development Variation Environment Monitoring to Analyze the Characteristics of the Composition of the Suite. (4th October 2022) - He, Yanan; Kang, Qin
Abstract : In order to better grasp the quintessence of Brahms's suite-style piano suite and guide researchers and music creators, this thesis takes Brahms's late representative work Fantasia Op.116 as the research object and attempts based on the perspective of environmental monitoring of development and changes to analyze creative individuality in his seven works as well as the unity of the whole structure under the "developing variation" through elaborating the theory of "developing variation, " the creative features of works in Fantasia Op.116, and the unity of the materials under the "developing variation" from the perspective of creative techniques. The thesis finds that, on the one hand, Brahms used pitch interval structural capacity, nontraditional harmony, personalized rhythmic counterpoint, and prose structure and other specific variation techniques, embodying individuation differences and expanding the techniques used in the classical period; on the other hand, he changed, derived, and extended the theme motivation in works, specifically embodying the using of "developing variation" in his seven works, which solves the problems of unity and interconnectedness among works and provides inspirations for the creation of piano suites by later composers.